2001
DOI: 10.2134/jeq2001.3031015x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Alkalinity Generation by Successive Alkalinity‐Producing Systems: Regression Analysis

Abstract: Use of successive alkalinity-producing systems (SAPS) for treatment of acidic mine drainage (AMD) has grown in recent years. However, inconsistent performance has hampered widespread acceptance of this technology. This research was conducted to determine the influence of system design and influent AMD chemistry on net alkalinity generation by SAPS. Monthly observations were obtained from eight SAPS cells in southern West Virginia and southwestern Virginia. Analysis of these data revealed strong, positive corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 10 publications
2
33
1
2
Order By: Relevance
“…The relationship is logarithmic, indicating that the most rapid alkalinity generation occurs in the first few hours and that the rate of limestone dissolution slows with time likely as water reaches saturation with respect to calcite (Rose 1999). This relationship was also noted by Jage et al (2001) in a review of five SAPS cells in West Virginia. Net alkalinity generation rates in our RAPS units were greatest at Sullivan Mine followed by Herbert Stream and Pike River.…”
Section: Sullivan Mine and Pike River Adit Rapsmentioning
confidence: 63%
See 1 more Smart Citation
“…The relationship is logarithmic, indicating that the most rapid alkalinity generation occurs in the first few hours and that the rate of limestone dissolution slows with time likely as water reaches saturation with respect to calcite (Rose 1999). This relationship was also noted by Jage et al (2001) in a review of five SAPS cells in West Virginia. Net alkalinity generation rates in our RAPS units were greatest at Sullivan Mine followed by Herbert Stream and Pike River.…”
Section: Sullivan Mine and Pike River Adit Rapsmentioning
confidence: 63%
“…This is likely due to the much higher acidity and lower pH at the Sullivan Mine and Pike River compared to the Herbert Stream, which can result in faster limestone dissolution rates, and therefore a strong response to increases in limestone contact residence times. Jage et al (2001) noted a similar positive relationship between influent acidity and net alkalinity generation and attributed this in part to the higher solubility of calcite under acidic conditions.…”
Section: Sullivan Mine and Pike River Adit Rapsmentioning
confidence: 76%
“…Reported VFW treatment efficiencies for acidity range from almost no treatment to 800 g m −2 day −1 (Jage et al 2000(Jage et al , 2001Ji et al 2008;Kepler and McCleary 1994;LaBar et al 2008;Rose 2003Rose , 2004aRose , b, 2006 formation and precipitation of metal sulfides, microbial generation of alkalinity by sulfate reduction reactions, metal exchange and complexation reactions, and continuous formation of carbonate alkalinity due to limestone dissolution under anoxic conditions. Therefore, AnWs are suitable for the treatment of net-acidic water.…”
Section: Vertical Flow Wetlandsmentioning
confidence: 99%
“…Nevertheless, other studies have demonstrated the incorporation of organic rich compost within a limestone-based treatment system can enhance alkalinity production because of organic matter oxidation, sulfate reduction, CO 2 production, and associated interaction with limestone (e.g. Amos and Younger 2003;Jage et al 2001;Thomas and Romanek 2002a, b;Watzlaf et al 2000Watzlaf et al , 2004. The compost may be particularly effective for treatment of AMD with high concentrations of dissolved ferric iron and aluminum (Jage et al 2001;Thomas and Romanek 2002b).…”
Section: Bell Discharge Treatment Systemmentioning
confidence: 99%
“…Amos and Younger 2003;Jage et al 2001;Thomas and Romanek 2002a, b;Watzlaf et al 2000Watzlaf et al , 2004. The compost may be particularly effective for treatment of AMD with high concentrations of dissolved ferric iron and aluminum (Jage et al 2001;Thomas and Romanek 2002b).…”
Section: Bell Discharge Treatment Systemmentioning
confidence: 99%